Fetal Alcohol Spectrum Disorders in a Pacific Southwest City: Maternal and Child Characteristics - Chambers, Christina D. (Alcohol Clin Exp Res, 2019)
BACKGROUND: There are limited data on the characteristics of children with fetal alcohol spectrum disorders (FASD) and their mothers from the general population in the United States. METHODS: During the 2012 and 2013 academic years, first-grade children in a large urban Pacific Southwest city were invited to participate in a study to estimate the prevalence of FASD. Children who screened positive on weight, height or head circumference ≤ 25(th) centile or on parental report of developmental concerns were selected for evaluation, along with a random sample of those who screened negative. These children were examined for dysmorphology and neurobehavior and their mothers or collateral sources were interviewed. Children were classified as fetal alcohol syndrome (FAS), partial fetal alcohol syndrome (pFAS), alcohol related neurodevelopmental disorder (ARND), or No FASD. RESULTS: A total of 854 children were evaluated; 5 FAS, 44 pFAS, 44 ARND, and 761 no FASD. Children with FAS or pFAS were more likely to have dysmorphic features, and 32/49 (65.3%) of those met criteria for neurobehavioral impairment on cognitive measures with or without behavioral deficits. In contrast, 28/44 (63.6%) of children with ARND met criteria on behavioral measures alone. Mothers of FASD children were more likely to recognize pregnancy later, be unmarried, and report other substance use or psychiatric disorders, but did not differ on age, socioeconomic status, education or parity. Mothers of FASD children reported more drinks/drinking day each trimester. The risk of FASD was elevated with increasing number of drinks/drinking day prior to pregnancy recognition, even at the level of 1 drink per day (adjusted odds ratio 3.802, 95% confidence interval 1.634, 8.374). CONCLUSION: Data from this general population sample in a large urban region in the U.S. demonstrate the variability of expression of FASD, and point to risk and protective factors for mothers in this setting.